KARAKTERISTIK ORGANOLEPTIK KOMPOS BERBAHAN DASAR LIMBAH BAGLOG JAMUR TIRAM DAN KOHE KAMBING - hadi, m syamsul; widyasworo, agustina; samur, salnan irba novaela (AVES: Jurnal Ilmu Peternakan, 2024)
The purpose of this research is to explore the production of compost from goat manure with the addition of oyster mushroom substrate (baglog) and EM4. Composting is an effective method of recycling organic waste and improving soil fertility, making it a vital aspect of sustainable agriculture. This study focuses on determining the best mixture of goat manure and baglog in producing high-quality compost, which could serve as an alternative to chemical fertilizers. The research method utilized involved distributing questionnaires to 47 panelists who were tasked with evaluating the quality of the compost based on three sensory attributes: texture, color, and odor. These attributes are critical indicators of compost maturity and usability in agricultural applications. Each treatment was repeated three times to ensure consistent and reliable results. The organoleptic (sensory) test results indicated that the best treatment was P2, which contained 50% goat manure and 50% baglog. This mixture produced compost with the most favorable characteristics in terms of texture, color, and odor compared to other treatments. The combination of organic materials appeared to complement each other well, creating a balanced compost suitable for improving soil quality and plant growth. It is recommended that future research include laboratory tests to analyze the nutrient composition of the compost more precisely. Additionally, field trials should be conducted to test the compost's effectiveness in various agricultural settings and crops, ensuring its practicality as a sustainable alternative to synthetic fertilizers